Examining the Information Efficiency of Indonesia Equity Market: Evidence from Earnings Announcements - Nainggolan, Rexon (International Journal of Economics and Financial Issues, 2024)
The main objective of this study is to examine the semi-strong form of market efficiency in the Indonesia Equity Market on publicly available information. The study uses a market model to analyze the significance of abnormal returns before and after earnings releases. It analyzes the cumulative average abnormal returns of the daily trades before and after the earnings release. The study reveals that there are no significant abnormal returns during the pre-announcement periods, suggesting that there is no significant leakage of information before the disclosures. An analysis of the post-announcement documents reveals a delay in the market response, indicating that the market is inefficient in rapidly and accurately transmitting the information from earnings releases to investors. It also observes significant abnormal returns within the initial week of the release periods and a post-earnings announcement drift of up to 30 days. The findings indicate that the market does not possess the attributes of a semi-strong form of market efficiency. The results imply that the market’s financial reporting processes have the potential for digital technology improvement to enhance transparency, accountability, and information efficiency within the market.